Basic and specific fitness tests for freestyle wrestlers realized in the Republic of Macedonia: A review of research - Gligorov, S.; Bogdanov, V. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: The main goal was to perform a review of previous studies the tests of which were applied to assess basic and situation-specific motor fitness/abilities of freestyle wrestlers in the Republic of Macedonia. The second goal was to draw some conclusions about the sample of respondents, application of basic and situation-specific motor tests, data processing methods, and outcomes of research. METHODS: The empirical method was applied to analyze all available articles and documents on this topic usage of basic and specific fitness tests for freestyle wrestlers. RESULTS: Based on the review and analysis of the research, we can conclude that all measurement procedures and all records of testing and application of methods for data processing in the analysed studies were in accordance with the standard methodological requirements that apply to these types of testings. In most applied tests a satisfactory degree of measurement features was determined. In freestyle wrestlers we determined a relatively clean and clear existence of the following structure of factors of the basic motor tests: explosive power, dynamometric force, coordination, strength (repetitive and static), balance, flexibility, frequency of movement. In the situation-specifi motor tests, four latent situation-specific motor dimensions were isolated: the factor of complex situation-specific ability in standing and parterre positions, the factor of situation-specific ability to perform complex techniques of throws, the factor of situa tion-specific ability to quickly perform complex tasks in situational martial bridge, factor of situational ability to quickly transition from standing to parterre and vice versa. Basic motor skills - coordination, dynamometric force, power (repetitive and static), frequency of movements, explosive power, balance, and greater flexibility have hierarchically dominant influence on the determination of individually isolated situation-specific latent motor factors. CONCLUSIONS: Based on a previous review research on this topic (Basic and specific fitness tests for freestyle wrestlers realized in Republic of Macedonia), it can be concluded that the application of multivariate methods is very important and useful for determining the factorial structure and measurement features, and for the establishment of relations between the basic motor tests and situation-specific motor tests in freestyle wrestlers. Basic motor skills - coordination, dynamometric force, power (repetitive and static), frequency of movements, explosive strength, balance and flexibility, have hierarchically dominant influence on performance in freestyle wrestling. The findings may find their application in the implementation to further research projects related to the treated problems and they can also be used in the talent identification and selection of young wrestlers, and in rational, objective and cost-effective planning and programming of training process for different age categories in martial clubs and national teams.